Preparation method of lithium ion battery electrolyte with efficient conductivity

By preparing an ionic liquid synergistic system with asymmetric cations and functionalized anions, gradient electrolyte structure, bio-based additives and polymer network structure, the problems of poor conductivity and poor electrochemical stability of traditional lithium-ion battery electrolytes are solved. Lithium-ion battery electrolyte that achieves high-efficiency conductivity and long life.

CN119361835AInactive Publication Date: 2025-01-24HUNAN DAJING NEW MATERIAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411909041.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrolyte of traditional lithium-ion batteries has poor conductivity, poor lithium-ion solvation, poor electrochemical stability, limited battery energy density and short battery cycle life.

Method used

A high -efficiency conductive lithium -ion battery electrolyte preparation method is used, including preparing ionic liquid with asymmetric yang ion and functional ion ions to mix with carbonate solvents to form an ionic liquid collaboration system to prepare the lithium salt and ionic conduction additives The thin -layer solution forms a gradient electrolyte structure by layer -by -layer sedimentation process, adds biological base additives, and causes a polymer to form a polymer network structure in the electrolyte. Finally, the template method is used to build a multi -scale channel structure.

Benefits of technology

It significantly improves the transmission rate of lithium ions, optimizes the solvents of lithium ions, enhances the electrical conductivity and electrochemical stability of the electrolyte, broaden the electrochemical window, and improve the energy density and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium ion battery electrolyte with efficient conductivity, and relates to the technical field of lithium ion battery electrolytes.The preparation method of the lithium ion battery electrolyte comprises the steps that S1, ionic liquid is prepared and then mixed with a carbonic ester solvent; s2, preparing a gradient electrolyte structure; s3, preparing a bio-based additive; s4, carrying out photo-initiation polymerization reaction to form a polymer network structure; s5, constructing a multi-scale pore channel structure by using a template method; step S6, carrying out filtering treatment on the prepared electrolyte; and S7, carrying out performance test and optimization on the electrolyte. According to the invention, the ionic liquid with asymmetric cations and functionalized anions is prepared and mixed with the carbonic ester solvent to form an ionic liquid synergistic system, so that the problems of poor conductivity of the electrolyte, non-ideal solvation of lithium ions, poor electrochemical stability, limited energy density of the battery and short cycle life of the battery can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery electrolyte, in particular to a method for preparing a lithium ion battery electrolyte with high efficiency and conductivity. Background Art

[0002] Traditional lithium-ion battery electrolyte preparation methods cannot effectively guide the orderly transmission of lithium ions, and cannot construct a stable solvation environment that is conducive to the release of lithium ions, resulting in frequent disordered collisions of lithium ions during transmission, excessive solvation energy, and easy decomposition of solvent molecules under high voltage. These problems further cause poor electrolyte conductivity, unsatisfactory lithium ion solvation, and poor electrochemical stability. The lithium-ion battery electrolyte preparation method of the present application can solve the problems of poor electrolyte conductivity, unsatisfactory lithium ion solvation, poor electrochemical stability, limited battery energy density, and short battery cycle life.

[0003] The defects of the existing lithium ion battery electrolyte preparation method are: Patent document JP5858234B2 discloses a lithium-ion battery electrolyte. The document mainly considers the problem of how to provide a lithium-ion battery electrolyte that can stably operate within an intermediate temperature range of 85 degrees Celsius or higher, but does not consider how to solve the problems of poor electrolyte conductivity, unsatisfactory lithium ion solvation, poor electrochemical stability, limited battery energy density, and short battery cycle life; US9490503B1 discloses a lithium-ion battery electrolyte formula. The document mainly considers how to improve the power performance at low temperatures, but does not consider how to solve the problems of poor interface compatibility between the electrolyte and the electrode of traditional lithium-ion batteries, the formation of lithium dendrites due to uneven deposition of lithium ions on the electrode surface, and poor low-temperature performance; Patent document JP6742329B2 discloses a high-voltage lithium-ion battery electrolyte system. The document mainly considers how to ensure electrochemical stability within a wide voltage range, but does not consider how to solve the problems of insufficient surface stability of traditional lithium-ion battery electrodes and high lithium-ion interface transmission resistance. Patent document CN103078139B discloses a lithium-ion battery electrolyte. The document mainly considers how to improve the graphite exfoliation of the anode pole piece and improve the lithium insertion and extraction performance of the anode pole piece, but does not consider how to solve the problems of poor mechanical stability, insufficient battery cycle stability and poor high temperature performance of traditional lithium-ion battery electrolytes. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a lithium-ion battery electrolyte with high efficiency and conductivity, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for preparing a lithium-ion battery electrolyte with high efficiency and conductivity, the method comprising: Step S1, preparing an ionic liquid having an asymmetric cation and a functionalized anion, and mixing the ionic liquid with a carbonate solvent to form an ionic liquid synergistic system; Step S2, preparing a thin layer solution rich in lithium salt and ion conductive additives, depositing the thin layer solution at the interface between the electrode and the electrolyte to form a thin layer through a layer-by-layer deposition process, and continuing to fill the main part of the electrolyte on the thin layer to prepare a gradient electrolyte structure; Step S3, preparing a bio-based additive and adding it to the electrolyte; Step S4, adding 1%-5% by mass of an acrylic acid ester monomer and 0.1%-0.5% by mass of a 1-hydroxycyclohexyl phenyl ketone photoinitiator to the electrolyte to perform a photoinitiated polymerization reaction to form a polymer network structure; Step S5, preparing a nano-silica template solution, and constructing a multi-scale pore structure using a template method; Step S6, filtering the prepared electrolyte; Step S7: testing and optimizing the performance of the electrolyte.

[0006] Preferably, the asymmetric cation is an imidazolium cation containing a long-chain alkyl substituent, and the alkyl chain length is 4-10 carbon atoms; The functionalized anion is a fluorine-containing organic anion having multiple coordination sites, and the coordination energy with the lithium ion is between -12 kJ / mol and -21 kJ / mol.

[0007] Preferably, step S1 further includes: Step S11: mixing the synthesized ionic liquid and the carbonate solvent in a volume ratio of 1:4-1:9, so that the cations of the ionic liquid and the lithium ions produce weak interactions to guide the orderly transmission of lithium ions, and the anions participate in the solvation shell construction to optimize the lithium ion solvation environment; Step S12: stirring and ultrasonically treating the mixed system, with a stirring speed of 330 rpm-470 rpm and an ultrasonic time of 32 min-56 min.

[0008] Preferably, the lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 1:1-3:1; The ion-conducting additive is an organic compound with a linear ether chain structure and a mass fraction of 10%-20%, the ether chain length is 3-6 oxygen atoms, and the lithium salt concentration is 2-5 times the lithium salt concentration of the main electrolyte.

[0009] Preferably, step S2 further includes: Step S21: The layer-by-layer deposition process has a deposition rate of 0.1 μm / s-0.3 μm / s, and the lithium salt concentration in the main electrolyte is 0.8 mol / L-1.2 mol / L.

[0010] Preferably, step S3 further includes: Step S31: reacting lignin with propylene oxide at a pH value of 10-12 to introduce hydroxyl groups, the reaction temperature is 62° C.-79° C., and the reaction time is 4.2-5.8 h to obtain hydroxylated lignin, wherein the hydroxyl content in each gram of modified lignin is 3 mmol-5 mmol; Step S32: introducing carboxyl groups by reacting hydroxylated lignin with maleic anhydride, the reaction temperature is 80° C.-100° C., the reaction time is 3.2 h-5.2 h, and the carboxyl content is 2 mmol-4 mmol, thereby obtaining a bio-based additive containing multiple active hydroxyl groups and carboxyl groups; Step S33: adding the bio-based additive to the electrolyte at a mass fraction of 0.5%-3%, and the molar ratio of the total number of hydroxyl groups and carboxyl groups of the additive to the lithium salt is 1:6-1:9.

[0011] Preferably, step S4 further includes: Step S41: an acrylic acid ester monomer is prepared by mixing hydroxyethyl acrylate and butyl acrylate in a molar ratio of 1:2-1:3; Step S42: inject the electrolyte with added monomers and photoinitiator into the battery shell, assemble the battery, and use light with a wavelength of 300nm-400nm to make the monomers polymerize on the electrode surface. The light intensity is 5mW / cm²-10mW / cm², and the illumination time is 3min-5min.

[0012] Preferably, step S5 further includes: Step S51: The nano-silica template has a mass fraction of 5%-10%, and is evenly mixed with an electrolyte. Polyvinylidene fluoride-hexafluoropropylene copolymer is added to the mixed solution as a polymer matrix, and the mass ratio of the polymer matrix to the electrolyte is 1:3-1:5. The polymer matrix is ​​dissolved by stirring and heating to form a gel precursor; Step S52: treating the gel precursor to remove the nano-silica template and form a gel electrolyte having interconnected nano-scale 2nm-20nm and micro-scale 0.5μm-5μm pores, by soaking in sodium hydroxide solution for 12h-24h and then washing and drying.

[0013] Preferably, step S6 further includes: Step S61: using a filter with a pore size of 0.2 μm-0.4 μm to preliminarily filter the electrolyte to remove large particle impurities, and passing the preliminarily filtered electrolyte through an ion exchange resin column; Step S62: The electrolyte treated by the ion exchange resin column is subjected to vacuum degassing treatment, the vacuum degree is -0.08MPa to -0.1MPa, and the degassing time is 10min-20min.

[0014] Preferably, step S7 further includes: Step S71: Using an electrochemical workstation to test the performance indicators of the electrolyte, including ionic conductivity, electrochemical window, lithium ion transfer number, thermal stability, viscosity and electrochemical stability Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares an ionic liquid having an asymmetric cation and a functionalized anion, and mixes it with a carbonate solvent to form an ionic liquid synergistic system. The weak interaction between the asymmetric cation and the lithium ion can effectively guide the orderly transmission of the lithium ion along a specific direction, reduce the disordered collision and scattering of the lithium ion during the transmission process, and thus significantly improve the transmission rate of the lithium ion. The functionalized anion participates in the construction of the solvation shell and can form a more stable coordination structure with the lithium ion. This stable coordination structure can not only reduce the solvation energy of the lithium ion, making it easier for the lithium ion to be freed from the solvation shell to participate in the electrochemical reaction, but also effectively prevent the decomposition of the solvent molecules under high voltage, thereby improving the electrochemical stability of the electrolyte. At the same time, the optimized solvation environment helps to reduce the formation of ion pairs in the electrolyte, increase the concentration of free lithium ions, and further improve the conductive properties of the electrolyte. The introduction of the ionic liquid synergistic system changes the electrochemical properties of the electrolyte, so that the electrochemical window of the electrolyte is widened. This means that the battery can withstand a higher voltage range during the charge and discharge process, so that electrode materials with a higher voltage platform can be selected to improve the energy density of the battery. At the same time, the wider electrochemical window also reduces the possibility of redox reactions in the electrolyte at high voltage, reduces side reactions inside the battery, and extends the cycle life of the battery. Therefore, it can solve the problems of poor electrolyte conductivity, unsatisfactory lithium ion solvation, poor electrochemical stability, limited battery energy density and short battery cycle life.

[0015] 2. The present invention prepares a thin layer solution rich in lithium salts and ion-conducting additives, adopts a layer-by-layer deposition process to form a gradient electrolyte structure, and constructs a special physical and chemical environment at the interface between the electrode and the electrolyte. This structure can effectively reduce the interfacial energy between the electrode and the electrolyte, promote the full contact and infiltration of the electrolyte and the electrode surface, and improve the interface compatibility. At the same time, the concentrations of lithium salts and ion-conducting additives in the gradient structure present a specific distribution at the interface, which makes the transmission of lithium ions at the interface smoother, accelerates the electrode reaction kinetics, and thus improves the charge and discharge efficiency and power performance of the battery. In the thin layer at the interface between the electrode and the electrolyte, the special structure rich in lithium salts and ion-conducting additives can regulate the deposition behavior of lithium ions on the electrode surface. By optimizing the concentration distribution and transmission path of lithium ions at the interface, lithium ions can be uniformly deposited on the electrode surface, avoiding excessive deposition of lithium ions in local areas to form lithium dendrites. The inhibition of lithium dendrites can not only improve the safety of the battery, prevent the occurrence of dangerous situations such as battery short circuit and thermal runaway, but also reduce the damage of lithium dendrite growth to the electrode material and extend the cycle life of the battery. The gradient electrolyte structure has unique advantages in low temperature environments. Due to its special composition and structure, it can maintain good ion conductivity and fluidity at low temperatures, reducing the freezing point and viscosity increase of the electrolyte. This allows lithium ions to be transmitted relatively smoothly between the electrode and the electrolyte at low temperatures, thereby effectively improving the battery's charge and discharge performance and cycle stability under low temperature conditions, and broadening the application temperature range of lithium-ion batteries. Therefore, it can solve the problems of poor interface compatibility between the electrolyte and the electrode of traditional lithium-ion batteries, the formation of lithium dendrites due to uneven deposition of lithium ions on the electrode surface, and poor low-temperature performance.

[0016] 3. The present invention prepares a bio-based additive containing multiple active hydroxyl and carboxyl groups and adds it to the electrolyte. The hydroxyl and carboxyl groups can chemically adsorb or chemically react with the active sites on the electrode surface to form a stable protective film. This protective film can effectively prevent direct contact between the electrode material and the electrolyte, reduce side reactions on the electrode surface, such as decomposition of the electrolyte, dissolution and corrosion of the electrode material, etc., thereby improving the chemical stability of the electrode surface and extending the service life of the electrode. The presence of the bio-based additive can improve the interfacial properties between the electrolyte and the electrode and reduce the transmission resistance of lithium ions at the interface. Its hydroxyl and carboxyl groups can interact with lithium ions, assist the adsorption and desorption process of lithium ions on the electrode surface, and promote the diffusion and transmission of lithium ions between the electrolyte and the electrode. This promotion effect can improve the rate performance of lithium-ion batteries, so that the battery can still maintain a high capacity and efficiency under high current charging and discharging conditions. The use of bio-based additives makes the electrolyte more biodegradable and environmentally friendly. Compared with traditional additives, bio-based additives are derived from renewable biomass resources. They cause less pollution to the environment during the waste treatment of batteries after use, which is in line with the current trend of green chemistry and sustainable development. This not only helps to reduce the impact of the battery industry on the environment, but also helps to enhance the social image and market competitiveness of enterprises. Therefore, it can solve the problems of insufficient surface stability of traditional lithium-ion battery electrodes and high lithium-ion interface transmission resistance.

[0017] 4. The present invention forms a polymer network structure by adding acrylate monomers and photoinitiators to the electrolyte for photoinitiated polymerization, which is interwoven with other components in the electrolyte to form a three-dimensional cross-linked network. This network structure can effectively improve the mechanical strength and toughness of the electrolyte, so that it can better resist the stress and strain caused by the volume change of the electrode during the battery charging and discharging process, prevent the leakage of the electrolyte and the damage to the internal structure of the battery, thereby improving the mechanical stability and safety of the battery. The existence of the polymer network structure and the multi-scale pore structure provides a rich and diverse transmission channel for lithium ions. The nanoscale and micron-scale pores are interconnected to form an efficient ion transmission network, making the transmission path of lithium ions in the electrolyte more tortuous and rich. This multi-scale pore structure can not only increase the number of lithium ion transmission channels, but also effectively reduce the activation energy of ion transmission and improve the ion transmission efficiency. At the same time, the existence of the pore structure can also accommodate the volume change of the electrolyte during the charging and discharging process, further improving the cycle stability of the battery. In a high temperature environment, the polymer network structure and the multi-scale pore structure can effectively inhibit the volatilization and decomposition of the electrolyte. The polymer network structure can bind the solvent molecules and lithium salts in the electrolyte inside its network, reducing their volatilization losses at high temperatures. At the same time, the multi-scale pore structure can provide a certain buffer space for the expansion of the electrolyte at high temperatures, preventing the electrolyte from causing excessive internal pressure in the battery due to volume expansion. This structural advantage enables the battery to maintain good performance and safety under high temperature conditions, extending the service life of the battery in high temperature environments. Therefore, it can solve the problems of poor mechanical stability of traditional lithium-ion battery electrolytes, insufficient battery cycle stability, and poor high temperature performance. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Embodiment 1: A method for preparing a lithium-ion battery electrolyte with high conductivity, the method comprising: Step S1, preparing an ionic liquid having an asymmetric cation and a functionalized anion, and mixing the ionic liquid with a carbonate solvent to form an ionic liquid synergistic system; The asymmetric cation is an imidazolium cation containing a long-chain alkyl substituent, and the alkyl chain length is 46 carbon atoms; The functionalized anion is a fluorine-containing organic anion having multiple coordination sites, and the coordination energy with the lithium ion is between -16 kJ / mol.

[0020] Step S1 also includes: Step S11: mixing the synthesized ionic liquid and the carbonate solvent in a volume ratio of 1:7, so that the cations of the ionic liquid and the lithium ions produce a weak interaction to guide the orderly transmission of lithium ions, and the anions participate in the solvation shell construction to optimize the solvation environment of lithium ions; Step S12: The mixed system is stirred and ultrasonically treated, with a stirring speed of 400 rpm and an ultrasonic time of 42 min.

[0021] Step S2, preparing a thin layer solution rich in lithium salt and ion conductive additives, depositing the thin layer solution at the interface between the electrode and the electrolyte to form a thin layer through a layer-by-layer deposition process, and continuing to fill the main part of the electrolyte on the thin layer to prepare a gradient electrolyte structure; The lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 2:1; The ion-conducting additive is an organic compound with a linear ether chain structure and a mass fraction of 16%. The ether chain length is 4 oxygen atoms, and the lithium salt concentration is 3 times the lithium salt concentration of the main electrolyte.

[0022] Step S2 also includes: Step S21: The layer-by-layer deposition process has a deposition rate of 0.2 μm / s and a lithium salt concentration of 1.0 mol / L in the main electrolyte.

[0023] Step S3, preparing a bio-based additive and adding it to the electrolyte; Step S3 also includes: Step S31: reacting lignin with propylene oxide at a pH of 11 to introduce hydroxyl groups, the reaction temperature is 72° C., the reaction time is 5.2 h, and hydroxylated lignin is obtained, wherein the hydroxyl content in each gram of modified lignin is 4 mmol; Step S32: introducing carboxyl groups by reacting hydroxylated lignin with maleic anhydride, the reaction temperature is 92° C., the reaction time is 4.5 h, and the carboxyl content is 3 mmol, thereby obtaining a bio-based additive containing multiple active hydroxyl groups and carboxyl groups; Step S33: adding the bio-based additive to the electrolyte at a mass fraction of 2%, and the molar ratio of the total number of hydroxyl groups and carboxyl groups of the additive to the lithium salt is 1:7.

[0024] Step S4, adding 3% by mass of an acrylic acid ester monomer and 0.3% by mass of a 1-hydroxycyclohexyl phenyl ketone photoinitiator to the electrolyte to perform a photoinitiated polymerization reaction to form a polymer network structure; Step S4 also includes: Step S41: an acrylic ester monomer is prepared by mixing hydroxyethyl acrylate and butyl acrylate in a molar ratio of 1:2.5; Step S42: inject the electrolyte with added monomers and photoinitiator into the battery shell, assemble the battery, and use light with a wavelength of 360nm to make the monomers polymerize on the electrode surface. The light intensity is 8mW / cm² and the illumination time is 4min.

[0025] Step S5, preparing a nano-silica template solution, and constructing a multi-scale pore structure using a template method; Step S5 also includes: Step S51: The nano-silica template has a mass fraction of 8%, and is evenly mixed with an electrolyte. Polyvinylidene fluoride-hexafluoropropylene copolymer is added to the mixed solution as a polymer matrix, and the mass ratio of the polymer matrix to the electrolyte is 1:4. The polymer matrix is ​​dissolved by stirring and heating to form a gel precursor; Step S52: treating the gel precursor to remove the nano-silica template and form a gel electrolyte with interconnected nano-scale 12nm and micro-scale 2.5μm pores, by soaking in sodium hydroxide solution for 18h and then washing and drying.

[0026] Step S6, filtering the prepared electrolyte; Step S6 also includes: Step S61: using a filter with a pore size of 0.3 μm to preliminarily filter the electrolyte to remove large particle impurities, and passing the preliminarily filtered electrolyte through an ion exchange resin column; Step S62: The electrolyte treated by the ion exchange resin column is subjected to vacuum degassing treatment, the vacuum degree is -0.09 MPa, and the degassing time is 15 minutes.

[0027] Step S7: testing and optimizing the performance of the electrolyte.

[0028] Step S7 also includes: Step S71: using an electrochemical workstation to test the performance indicators of the electrolyte, including ionic conductivity, electrochemical window, lithium ion transference number, thermal stability, viscosity and electrochemical stability.

[0029] Embodiment 2: A method for preparing a lithium-ion battery electrolyte with high conductivity, the method for preparing a lithium-ion battery electrolyte comprising: Step S1, preparing an ionic liquid having an asymmetric cation and a functionalized anion, and mixing the ionic liquid with a carbonate solvent to form an ionic liquid synergistic system; The asymmetric cation is an imidazolium cation containing a long-chain alkyl substituent, and the alkyl chain length is 8 carbon atoms; The functionalized anion is a fluorine-containing organic anion having multiple coordination sites, and the coordination energy with the lithium ion is between -19 kJ / mol.

[0030] Step S1 also includes: Step S11: mixing the synthesized ionic liquid and the carbonate solvent in a volume ratio of 1:8, so that the cations of the ionic liquid and the lithium ions produce a weak interaction to guide the orderly transmission of lithium ions, and the anions participate in the solvation shell construction to optimize the lithium ion solvation environment; Step S12: The mixed system is stirred and ultrasonically treated, with a stirring speed of 450 rpm and an ultrasonic time of 50 min.

[0031] Step S2, preparing a thin layer solution rich in lithium salt and ion conductive additives, depositing the thin layer solution at the interface between the electrode and the electrolyte to form a thin layer through a layer-by-layer deposition process, and continuing to fill the main part of the electrolyte on the thin layer to prepare a gradient electrolyte structure; The lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 2.5:1; The ion-conducting additive is an organic compound with a linear ether chain structure and a mass fraction of 18%. The ether chain length is 4 oxygen atoms, and the lithium salt concentration is 4 times the lithium salt concentration of the main electrolyte.

[0032] Step S2 also includes: Step S21: The layer-by-layer deposition process has a deposition rate of 0.25 μm / s and a lithium salt concentration of 1.1 mol / L in the main electrolyte.

[0033] Step S3, preparing a bio-based additive and adding it to the electrolyte; Step S3 also includes: Step S31: reacting lignin with propylene oxide at a pH of 11.5 to introduce hydroxyl groups, the reaction temperature is 76° C., the reaction time is 5.5 h, and hydroxylated lignin is obtained, and the hydroxyl content in each gram of modified lignin is 4.5 mmol; Step S32: introducing carboxyl groups by reacting hydroxylated lignin with maleic anhydride at a reaction temperature of 96° C. for a reaction time of 4.8 h, so that the carboxyl content is 3.5 mmol, and a bio-based additive containing multiple active hydroxyl groups and carboxyl groups is obtained; Step S33: adding the bio-based additive to the electrolyte at a mass fraction of 2.5%, and the molar ratio of the total number of hydroxyl groups and carboxyl groups of the additive to the lithium salt is 1:6.

[0034] Step S4, adding 5% by mass of an acrylic acid ester monomer and 0.5% by mass of a 1-hydroxycyclohexyl phenyl ketone photoinitiator to the electrolyte to perform a photoinitiated polymerization reaction to form a polymer network structure; Step S4 also includes: Step S41: an acrylic ester monomer is prepared by mixing hydroxyethyl acrylate and butyl acrylate in a molar ratio of 1:2.8; Step S42: inject the electrolyte with added monomers and photoinitiator into the battery shell, assemble the battery, and use light with a wavelength of 380nm to make the monomers polymerize on the electrode surface. The light intensity is 9mW / cm² and the illumination time is 4.5min.

[0035] Step S5, preparing a nano-silica template solution, and constructing a multi-scale pore structure using a template method; Step S5 also includes: Step S51: The nano-silica template has a mass fraction of 9%, and is evenly mixed with an electrolyte. Polyvinylidene fluoride-hexafluoropropylene copolymer is added to the mixed solution as a polymer matrix, and the mass ratio of the polymer matrix to the electrolyte is 1:4.5. The polymer matrix is ​​dissolved by stirring and heating to form a gel precursor; Step S52: treating the gel precursor to remove the nano-silica template and form a gel electrolyte with interconnected nano-scale 16nm and micro-scale 3.5μm pores, by soaking in a sodium hydroxide solution for 20 hours and then washing and drying.

[0036] Step S6, filtering the prepared electrolyte; Step S6 also includes: Step S61: using a filter with a pore size of 0.35 μm to preliminarily filter the electrolyte to remove large particle impurities, and passing the preliminarily filtered electrolyte through an ion exchange resin column; Step S62: The electrolyte treated by the ion exchange resin column is subjected to vacuum degassing treatment, the vacuum degree is -0.095 MPa, and the degassing time is 18 minutes.

[0037] Step S7: testing and optimizing the performance of the electrolyte.

[0038] Step S7 also includes: Step S71: using an electrochemical workstation to test the performance indicators of the electrolyte, including ionic conductivity, electrochemical window, lithium ion transference number, thermal stability, viscosity and electrochemical stability.

[0039] Embodiment 3: A method for preparing a lithium-ion battery electrolyte with high conductivity, the method for preparing a lithium-ion battery electrolyte comprising: Step S1, preparing an ionic liquid having an asymmetric cation and a functionalized anion, and mixing the ionic liquid with a carbonate solvent to form an ionic liquid synergistic system; The asymmetric cation is an imidazolium cation containing a long-chain alkyl substituent, and the alkyl chain length is 5 carbon atoms; The functionalized anion is a fluorine-containing organic anion having multiple coordination sites, and the coordination energy with the lithium ion is between -14 kJ / mol.

[0040] Step S1 also includes: Step S11: mixing the synthesized ionic liquid and the carbonate solvent in a volume ratio of 1:6, so that the cations of the ionic liquid and the lithium ions produce a weak interaction to guide the orderly transmission of lithium ions, and the anions participate in the solvation shell construction to optimize the lithium ion solvation environment; Step S12: The mixed system is stirred and ultrasonically treated, with a stirring speed of 350 rpm and an ultrasonic time of 40 min.

[0041] Step S2, preparing a thin layer solution rich in lithium salt and ion conductive additives, depositing the thin layer solution at the interface between the electrode and the electrolyte to form a thin layer through a layer-by-layer deposition process, and continuing to fill the main part of the electrolyte on the thin layer to prepare a gradient electrolyte structure; The lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 1:1; The ion-conducting additive is an organic compound with a linear ether chain structure and a mass fraction of 12%. The ether chain length is 3 oxygen atoms, and the lithium salt concentration is twice the lithium salt concentration of the main electrolyte.

[0042] Step S2 also includes: Step S21: The layer-by-layer deposition process has a deposition rate of 0.15 μm / s and a lithium salt concentration of 0.9 mol / L in the main electrolyte.

[0043] Step S3, preparing a bio-based additive and adding it to the electrolyte; Step S3 also includes: Step S31: reacting lignin with propylene oxide at a pH of 10.5 to introduce hydroxyl groups, the reaction temperature is 66° C., the reaction time is 5 h, and hydroxylated lignin is obtained, and the hydroxyl content in each gram of modified lignin is 3.2 mmol; Step S32: introducing carboxyl groups by reacting hydroxylated lignin with maleic anhydride at a reaction temperature of 86° C. for a reaction time of 3.5 h, so that the carboxyl content is 2.2 mmol, and a bio-based additive containing multiple active hydroxyl groups and carboxyl groups is obtained; Step S33: adding the bio-based additive to the electrolyte at a mass fraction of 1.5%, and the molar ratio of the total number of hydroxyl groups and carboxyl groups of the additive to the lithium salt is 1:8.

[0044] Step S4, adding 1% by mass of an acrylic acid ester monomer and 0.1% by mass of a 1-hydroxycyclohexyl phenyl ketone photoinitiator to the electrolyte to perform a photoinitiated polymerization reaction to form a polymer network structure; Step S4 also includes: Step S41: an acrylic ester monomer is prepared by mixing hydroxyethyl acrylate and butyl acrylate in a molar ratio of 1:2.2; Step S42: inject the electrolyte with added monomers and photoinitiator into the battery shell, assemble the battery, and use light with a wavelength of 320nm to make the monomers polymerize on the electrode surface. The light intensity is 6mW / cm² and the illumination time is 3.5min.

[0045] Step S5, preparing a nano-silica template solution, and constructing a multi-scale pore structure using a template method; Step S5 also includes: Step S51: The nano-silica template has a mass fraction of 6%, and is evenly mixed with an electrolyte. Polyvinylidene fluoride-hexafluoropropylene copolymer is added to the mixed solution as a polymer matrix, and the mass ratio of the polymer matrix to the electrolyte is 1:3.5. The polymer matrix is ​​dissolved by stirring and heating to form a gel precursor; Step S52: treating the gel precursor to remove the nano-silica template and form a gel electrolyte having interconnected nano-scale 6nm and micro-scale 1.2μm pores, the treatment method being to soak in a sodium hydroxide solution for 15h and then wash and dry.

[0046] Step S6, filtering the prepared electrolyte; Step S6 also includes: Step S61: using a filter with a pore size of 0.25 μm to preliminarily filter the electrolyte to remove large particle impurities, and passing the preliminarily filtered electrolyte through an ion exchange resin column; Step S62: The electrolyte treated by the ion exchange resin column is subjected to vacuum degassing treatment, the vacuum degree is -0.085 MPa, and the degassing time is 12 minutes.

[0047] Step S7: testing and optimizing the performance of the electrolyte.

[0048] Step S7 also includes: Step S71: using an electrochemical workstation to test the performance indicators of the electrolyte, including ionic conductivity, electrochemical window, lithium ion transference number, thermal stability, viscosity and electrochemical stability.

[0049] Example 4: Step S1: An ionic liquid is synthesized using imidazole cations and anions without long-chain alkyl groups, and mixed with a carbonate solvent in a volume ratio of 1:4, with a stirring speed of 250 rpm and an ultrasonic time of 20 min.

[0050] Step S2: The lithium salt is only lithium hexafluorophosphate, without ion-conducting additives, the deposition rate is 0.05 μm / s, and the lithium salt concentration of the main electrolyte is 0.6 mol / L.

[0051] Step S3: Preparation and addition of bio-free additives.

[0052] Step S4: No addition of acrylic monomers and photoinitiators.

[0053] Step S5: No nano-silica template solution treatment.

[0054] Step S6: Filter once using a filter with a pore size of 0.5 μm.

[0055] Step S7: Perform performance testing and optimization on the electrolyte.

[0056] The remaining specific steps are the same as those in the first embodiment.

[0057] Example 5: The performance indicators of the electrolytes prepared in Example 1, Example 2, Example 3 and Example 4 were tested using an electrochemical workstation, including ionic conductivity, electrochemical window, lithium ion transference number, thermal stability, viscosity and electrochemical stability.

[0058] The test results of Example 1 include: ion conductivity of 12mS / cm, electrochemical window of 4.8V, lithium ion migration number of 0.52, slight decomposition at 200°C, viscosity of 1.8mPa·s, capacity retention rate of more than 90% in long-term cycle test, and coulombic efficiency of about 98% after 500 cycles, showing good electrochemical stability.

[0059] The test results of Example 2 include: ionic conductivity is 13mS / cm, electrochemical window is 5.0V, lithium ion migration number is 0.55, At 210°C, decomposition signs began to appear, and the viscosity was 2.0 mPa·s. After 500 cycles, the capacity retention rate was about 92%, and the Coulomb efficiency was stable at about 99%. The electrochemical stability was good and slightly better than that of Example 1.

[0060] The test results of Example 3 include: ionic conductivity of about 10mS / cm, electrochemical window of 4.6V, lithium ion migration number of 0.48, thermal stability of starting to decompose at 190°C, viscosity of 1.6mPa·s, capacity retention rate of about 88% after 500 cycles, coulombic efficiency of about 97%, and electrochemical stability. It is acceptable, but weaker than that of Example 1 and Example 2.

[0061] The test results of Example 4 include: ionic conductivity of 8 mS / cm, electrochemical window of 4.2 V, lithium ion migration number of 0.40, decomposition began at 180°C, thermal stability was poor, viscosity was 1.4 mPa·s, and after 300 cycles, the capacity retention rate was only about 70%, the coulombic efficiency was about 95%, the electrochemical stability was significantly lower than that of other embodiments, and the cycle life was short.

[0062] Embodiments 1, 2, and 3 all show good performance in ionic conductivity, electrochemical window, lithium ion migration number, thermal stability, viscosity, and electrochemical stability through the synergistic system of ionic liquids, gradient electrolyte structure, bio-based additives, and polymer network structure, and can meet the requirements of high-performance electrolytes for lithium-ion batteries. However, due to the lack of additives and structural design, the performance indicators of embodiment 4 are obviously poor, and the effects comparable to those of the first three embodiments cannot be achieved, which highlights the importance and necessity of various functional components and structures in improving the performance of lithium-ion battery electrolytes.

[0063] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a highly conductive lithium-ion battery electrolyte, characterized in that: The method for preparing a lithium-ion battery electrolyte comprises: Step S1, preparing an ionic liquid having an asymmetric cation and a functionalized anion, and mixing the ionic liquid with a carbonate solvent to form an ionic liquid synergistic system; Step S2, preparing a thin layer solution rich in lithium salt and ion conductive additives, depositing the thin layer solution at the interface between the electrode and the electrolyte to form a thin layer through a layer-by-layer deposition process, and continuing to fill the main part of the electrolyte on the thin layer to prepare a gradient electrolyte structure; Step S3, preparing a bio-based additive and adding it to the electrolyte; Step S4, adding 1%-5% by mass of an acrylic acid ester monomer and 0.1%-0.5% by mass of a 1-hydroxycyclohexyl phenyl ketone photoinitiator to the electrolyte to perform a photoinitiated polymerization reaction to form a polymer network structure; Step S5, preparing a nano-silica template solution, and constructing a multi-scale pore structure using a template method; Step S6, filtering the prepared electrolyte; Step S7: testing and optimizing the performance of the electrolyte.

2. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: The asymmetric cation is an imidazolium cation containing a long-chain alkyl substituent, and the alkyl chain length is 4-10 carbon atoms; The functionalized anion is a fluorine-containing organic anion having multiple coordination sites, and the coordination energy with the lithium ion is between -12 kJ / mol and -21 kJ / mol.

3. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S1 also includes: Step S11: mixing the synthesized ionic liquid and the carbonate solvent in a volume ratio of 1:4-1:9, so that the cations of the ionic liquid and the lithium ions produce weak interactions to guide the orderly transmission of lithium ions, and the anions participate in the solvation shell construction to optimize the lithium ion solvation environment; Step S12: stirring and ultrasonically treating the mixed system, with a stirring speed of 330 rpm-470 rpm and an ultrasonic time of 32 min-56 min.

4. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: The lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a molar ratio of 1:1-3:1; The ion-conducting additive is an organic compound with a linear ether chain structure and a mass fraction of 10%-20%, the ether chain length is 3-6 oxygen atoms, and the lithium salt concentration is 2-5 times the lithium salt concentration of the main electrolyte.

5. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S2 also includes: Step S21: The layer-by-layer deposition process has a deposition rate of 0.1 μm / s-0.3 μm / s, and the lithium salt concentration in the main electrolyte is 0.8 mol / L-1.2 mol / L.

6. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S3 also includes: Step S31: reacting lignin with propylene oxide at a pH value of 10-12 to introduce hydroxyl groups, the reaction temperature is 62° C.-79° C., and the reaction time is 4.2-5.8 h to obtain hydroxylated lignin, wherein the hydroxyl content in each gram of modified lignin is 3 mmol-5 mmol; Step S32: introducing carboxyl groups by reacting hydroxylated lignin with maleic anhydride, the reaction temperature is 80° C.-100° C., the reaction time is 3.2 h-5.2 h, and the carboxyl content is 2 mmol-4 mmol, thereby obtaining a bio-based additive containing multiple active hydroxyl groups and carboxyl groups; Step S33: adding the bio-based additive to the electrolyte at a mass fraction of 0.5%-3%, and the molar ratio of the total number of hydroxyl groups and carboxyl groups of the additive to the lithium salt is 1:6-1:

9.

7. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S4 also includes: Step S41: an acrylic acid ester monomer is prepared by mixing hydroxyethyl acrylate and butyl acrylate in a molar ratio of 1:2-1:3; Step S42: inject the electrolyte with added monomers and photoinitiator into the battery shell, assemble the battery, and use light with a wavelength of 300nm-400nm to make the monomers polymerize on the electrode surface. The light intensity is 5mW / cm²-10mW / cm², and the illumination time is 3min-5min.

8. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S5 also includes: Step S51: The nano-silica template has a mass fraction of 5%-10%, and is evenly mixed with an electrolyte. Polyvinylidene fluoride-hexafluoropropylene copolymer is added to the mixed solution as a polymer matrix, and the mass ratio of the polymer matrix to the electrolyte is 1:3-1:

5. The polymer matrix is ​​dissolved by stirring and heating to form a gel precursor; Step S52: treating the gel precursor to remove the nano-silica template and form a gel electrolyte having interconnected nano-scale 2nm-20nm and micro-scale 0.5μm-5μm pores, by soaking in sodium hydroxide solution for 12h-24h and then washing and drying.

9. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S6 also includes: Step S61: using a filter with a pore size of 0.2 μm-0.4 μm to preliminarily filter the electrolyte to remove large particle impurities, and passing the preliminarily filtered electrolyte through an ion exchange resin column; Step S62: The electrolyte treated by the ion exchange resin column is subjected to vacuum degassing treatment, the vacuum degree is -0.08MPa to -0.1MPa, and the degassing time is 10min-20min.

10. The method for preparing a highly conductive lithium-ion battery electrolyte according to claim 1, characterized in that: Step S7 also includes: Step S71: using an electrochemical workstation to test the performance indicators of the electrolyte, including ionic conductivity, electrochemical window, lithium ion transference number, thermal stability, viscosity and electrochemical stability.

Citation Information

Patent Citations

  • Lithium-ion battery electrolyte

    CN103078139B

  • Electrolyte for Lithium-Ion Batteries

    JP5858234B2

  • Electrolyte systems for high-voltage lithium-ion batteries

    JP6742329B2

  • Electrolyte formulations for lithium ion batteries

    US9490503B1

  • Lithium ion battery

    CN107528086A